Natural feed additive of Macleaya cordata: safety assessment in rats a 90-day feeding experiment - Zdarilova, Adela; Vrublova, Eva; Vostalova, Jitka; Klejdus, Borivoj; Stejskal, David; Proskova, Jitka; Kosina, Pavel; Svobodova, Alena; Vecera, Rostislav; Hrbac, Jan; Cernochova, Drahomira; Vicar, Jaroslav; et al. (Food and chemical toxicology, 2008)
Macleaya cordata (Willd.) (Papaveraceae) is used as an active component in the natural feed additive Sangrovit. Sangrovit contains mixture of the intact aerial parts and the fraction of quaternary benzo[c]phenanthridine alkaloids from M. cordata (FQBA). In a 90-day pilot toxicity trial, Sangrovit and the FQBA were tested for safety. Male Wistar rats were fed for 90 days with 100, 7000 or 14000mg of Sangrovit or 600mg of FQBA in 1kg of feed. Body and organ weights, clinical chemistry and hematology markers, oxidative stress parameters, morphological structure of tongue, liver, ileum, kidney and heart samples, and total cytochrome P450 in liver were monitored. The results showed no statistically significant alterations in any parameter between control and treated animals, except for the group treated with 14000ppm Sangrovit that resulted in elevation of reduced glutathione level and superoxide dismutase activity in liver.
Keywords: tkáňová distribuce; velikost orgánu; oxidační stres; Feces; Male; Rats, Wistar; Organ Size; Drugs, Chinese Herbal; přijímání potravy; Animal Feed; Tissue Distribution; vysokoúčinná kapalinová chromatografie; Benzophenanthridines; pilotní projekty; benzofenantridiny; mužské pohlaví; krevní obraz; potkani Wistar; Eating; krmivo pro zvířata; Body Weight; dieta; Chromatography, High Pressure Liquid; krysa rodu Rattus; Blood Cell Count; systém (enzymů) cytochromů P-450; Animals; potravinářské přísady; léky rostlinné čínské; játra; Cytochrome P-450 Enzyme System; isochinoliny; zvířata; Rats; Food Additives; Diet; Isoquinolines; Liver; Pilot Projects; Papaveraceae; Oxidative Stress; feces; tělesná hmotnost